Prevalence of constitutive and inducible clindamycin resistance among clinical isolates of Staphylococcus aureus in a tertiary care institute in North India - Shetty, Jeevan; Afroz, Zarrin (International Journal of Research in Medical Sciences, 2017)
Background: Clindamycin is an important drug used in the treatment of Methicillin Sensitive Staphylococcus aureus (MSSA) as well as in Methicillin-resistant Staphylococcus aureus (MRSA) infections. This drug is widely used in the treatment of skin and soft tissue infections caused by them. Therapeutic failure caused by macrolide-lincosamine-streptogramin B constitutive and inducible clindamycin resistance (MLSBc and MLSBi) is being more commonly reported. Methods: The present study was conducted over a period of six months from October 2016 to March 2017 to know the incidence of MLSBc and MLSBi in Staphylococcus aureus (S. aureus) isolates obtained in our hospital by D-test as per CLSI guidelines. A total of 130 isolates of S.aureus were obtained from different clinical specimens which included pus/ wound swab (n=266), urine (n=577), sputum (n=225), blood (n=221), throat swab (n=71), ear/eye discharge (n=21), high vaginal swab (n=20) and body fluids (n=50). All the isolates were subjected to antibiotic sensitivity testing by Kirby Bauer’s disc diffusion method. Amoxyclav, Erythromycin, Clindamycin, Co-trimoxazole, Tetracycline, Ofloxacin, Gentamicin, Linezolid and Vancomycin were the antibiotics used. Results: Out of 130 (8.9%) isolates of S. aureus obtained from 1451 clinical samples, 82 (63.1%) were found to be MSSA and 48 (36.9%) were MRSA. Among S. aureus, 43 (33.1%) isolates showed MLSBc resistance, 22 (16.9%) isolates showed MLSBi resistance and 20 (15.4%) isolates showed MS phenotype. The remaining 45 (34.6%) isolates remained sensitive to Erythromycin. Among MSSA, MLSBc were observed in 18 (22%) isolates and MLSBi in 9 (11%) while in MRSA, MLSBc were observed in 25 (52.1%) isolates and MLSBi in 13 (27.1%) isolates. Almost all clinical isolates showed 100% sensitivity to Vancomycin and Linezolid in routine antibiotic susceptibility testing. Both MLSBc and MLSBi resistance was significantly higher (p<0.05) in MRSA than in MSSA. Conclusions: The study emphasizes the importance of conducting D test along with routine antibiotic susceptibility testing for better utilization of clindamycin in S. aureus infections.